PENDIDIKAN LINGKUNGAN HIDUP DALAM PERSPEKTIF ISLAM - PURWIDIANTO, PURWIDIANTO (Jurnal Pendidikan Islam, 2017)
This research aims to get a deep understanding about  Islam as a kaffah. For all this appears the understanding that Islam only deals with matters relating to human relationships to oneness of god . such understanding has actually narrowed the meaning and scope of the true teachings of Islam, which in turn affected the behavior of Muslims. Though there are many verses of the Quran or Hadith that tells Muslims to maintain and keep the environment. it is enough to be the base of the importance of maintenance of the environment. But in reality we are also faced the meaning of religious terms is not touching the maintenance of the environment. For that in the future need to formulate Islamic teachings, both in the field of tafsir, hadith, shariah related to the environment, so the maintenance of environmental sustainability is an integral part in Islamic dawah. Keywords ; Environmental Education, Living Environment